Validation of the Safe at Home Screening with Adults Who Have Acquired Brain Injury. Issue 1 (2nd January 2016) - Robnett, Regula H.; Bliss, Stephanie; Buck, Kari; Dempsey, Jennifer; Gilpatric, Heidi; Michaud, Katherine
ABSTRACT: The Safe at Home Screening (SAH) is an occupational therapy assessment tool designed to quickly assess home safety awareness and skills through the use of mock hazardous situations in a kitchen setting. The SAH has been standardized on community-dwelling adults. This research project involves psychometric analyses using the SAH on a sample of adults with acquired brain injuries (ABI; N = 31), and compares their SAH outcome scores with those of the Kohlman Evaluation of Living Skills (KELS). The scores on the two tests were found to be moderately correlated. An aspect of content validity was explored by asking the clients' occupational therapists to make predictions about their clients' functioning in the realm of home safety. Correlations between the expert opinions of potential client scores and actual SAH test scores were moderate.